Regional brain volumes and symptom severity in body dysmorphic disorder - Feusner, Jamie D. (2009)
Body dysmorphic disorder (BDD) is a severe psychiatric condition in which individuals are preoccupied with perceived defects in their appearance. Little is known of the pathophysiology or neurobiology of BDD. Recent evidence from a functional MRI study examining visual processing of faces demonstrated abnormal activation patterns in regions including left-sided inferior frontal gyrus (IFG) and amygdala. To investigate morphometric abnormalities we compared brain volumes from high-resolution T1 magnetic resonance images of twelve unmedicated subjects with BDD to twelve matched controls using voxel-based morphometry (VBM). In addition, we compared volumes in specific regions of interest including the IFG, amygdala, caudate, and total grey and white matter and examined correlations with symptom severity. VBM revealed no statistically significant volumetric differences, nor were there significant differences in any of the regions of interest. However, there were significant positive correlations between scores on the BDD version of the Yale-Brown Obsessive-Compulsive Disorder Scale (BDD-YBOCS) and volumes of the left IFG (r=0.69) and the right amygdala (r=0.54). These findings of correlations between BDD symptom severity and volumes of the left IFG and right amygdala are in concordance with the involvement of these regions in pathological face processing, which may contribute to the primary symptomatology.